Analysis of Mn accumulation onto plants in urban areas - AHMİDA SALEH, Elnaji Abdulaziz; IŞINKARALAR, Öznur (Kastamonu University, 2022)
The biggest problem in dense cities is air pollution and the damage to the environment caused by vehicles. Roadside landscape plants are exposed to pollutants, especially in small urban centers, which are caused by congested traffic. According to the type of landscape plants, being a good biomonitor varies according to their adsorbing capacity of pollutants. Fe and Mn are the leading pollutants originating from emissions. They are selected within the study and have various negative effects on plants in high concentrations. This study aimed to determine the Mn concentration changes according to organ and washing status and location of selected commonly used 14 landscape species in parks. The heavy metal holding capacity of 14 species used was compared the Mn concentration changed significantly depending on the factors evaluated to adsorb them. Chamaecyparis lawsoniana (A. Murr.) Parl. and Photinia serrulata Lindl. Where the highest values are obtained, they can reduce Mn pollution. Schinus molle L. is a suitable type that can monitor and mitigate the Mn concentration in the air.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water